Pelatihan dan Pendampingan Aplikasi Keuangan Buku Kas pada Angkringan Mas Eko di Kelurahan Condongcatur - Hanna Renita Putri; Nugraeni Nugraeni (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Service activities are carried out to provide assistance and training on the importance of accounting and financial statements to determine the company's performance in terms of finance by utilizing current technological advances. Service activities were carried out at Angkringan Mas Eko in Condongcatur sub-district, Depok District, Sleman Regency. The reason for the dedication due to the lack of competence of business owners in bookkeeping reports in the business being run. The method used in this activity is a method of mentoring and direct training in preparing financial statements using the BukuKas application for business actors. Considered successful when business actors are able to understand the differences before and after being given assistance and training. From the results of the dedication of business actors, they understand the importance of making structured financial statement bookkeeping, by utilizing the BukuKas financial application and alsothe understanding of business owner regarding financial reports that will be prepared in the following year